Keselamatan dan Kesehatan Kerja serta Pengaruhnya terhadap Kinerja (Studi pada Karyawan PT PG. Gempol Kerep Mojokerto) - Rifai, M. (Jurnal Aplikasi Manajemen, 2009)
Research aims at: (1) explaining the significant effect between variables of work environment, working method, preventive and curative processes simultaneously on the performance of the employee of Gempol Sugar Plant, Kerep, Mojokerto; (2) illuminating the significant effect between variables of work environment, working method, preventive and curative processes partially on the performance of the employee of Gempol Sugar Plant, Kerep, Mojokerto. Type of research may be Explanatory Research. Population of research includes all employees of Gempol Sugar Plant, Kerep, Mojokerto in 2008, especially 590 engineering employees. Research sample submits to 86 respondents. Research instrument relates to questionnaire. Analysis tool uses Multiple Regression supported by F-test and t-test. Results of analysis indicate that simultaneously and partially, the independent variables comprise to work environment (X1), working method (X2), preventive effort (X3), and curative effort (X4). These variables have significant effect on the dependent variable of employee performance (Y) by F significance (0.000 < 0.05). Strong relationship emerges between the independent variables (work environment, working method, preventive effort and curative effort) and the dependent variable (employee performance) as indicated by R rate (correlation coefficient) of 0.789.Keywords: Safety, Work Health, Performance